Interfacial precipitation and clogging in straight capillaries - Pal, Sayan; Kulkarni, Amol A. (Chemical Engineering Science, 2016)
Clogging of straight capillaries during interfacial precipitation (of common salt from saturated salt solution and acetone) was studied for a range of conditions that result in different flow regimes. The particle formation and clogging was explored using the images obtained by tracking a moving slug in real time. The flow regimes varied along the capillary length due to continuous mass transfer of acetone to water resulting in elongation of continuous phase slugs. In the slug flow regime, the precipitated particles formed solid shells/hemi spherical caps at the rear of acetone slugs, which eventually get detached from the interface. In the wavy parallel flow regime, where the interface is not flat, salting out was almost instantaneous and it led to faster clogging of the channels. Smaller Ca, i.e. lower flow rates or the use of smaller capillary length or using continuous fluid of relatively higher viscosity or lower interfacial tension can help to avoid or delay clogging. Formation of cohesive shells at the rear of a slug delayed clogging in the capillaries by delaying settling of individual particles. Parallel flow regime with a flat interface delayed the clogging significantly due to poor mass transfer as well as higher superficial velocities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Clogging time; Flow regime; Interfacial precipitation; Micro-capillary; Porous shells; slug flow

Impingement dynamics of jets in a confined impinging jet reactor - Pal, Sayan; Madane, Ketan; Mane, Mayur; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2021)
The interaction of two impinging liquid jets in a confined impinging jet reactor (CUR) is explored. Multiphase flow simulations were performed using the volume of fluids (VOF) approach to investigate the impingement dynamics of liquid impinging jets, and single-phase CFD simulations have been performed to understand the turbulence and the mixing performance in the system. At identical inlet velocities, the liquid sheet formed on the impingement axis was found to move toward the liquid jet inlet of the lesser density fluid until reaching equilibrium. The formation and transient movement of liquid sheets are characterized for different jet velocities. An improved reactor geometry is proposed that reduces the wall effect on sheet formation and wall deposition on discharge points of jets. Upon breaking away from the impinging film, the two liquid phases are found to be intertwined in the form of ligaments and droplets after fragmentation of the sheet, providing a higher interfacial confirmed by performing high-throughput continuous antisolvent precipitation.